2020
DOI: 10.1016/j.ajogmf.2020.100163
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic vaginal Candida colonization and adverse pregnancy outcomes including preterm birth: a systematic review and meta-analysis

Abstract: During pregnancy, vaginal colonization by Candida spp is common. Some studies suggest an association between asymptomatic vaginal Candida colonization and adverse pregnancy outcomes, but the evidence is inconsistent. This review aimed to systematically review the association between asymptomatic vaginal colonization by Candida spp and adverse pregnancy outcomes, including preterm birth. DATA SOURCES: We searched Ovid MEDLINE, Ovid Embase, and the Cochrane Central Register of Controlled Trials from inception to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Although metronidazole is safe for use in the first trimester of pregnancy, there is concern that treatment of T. vaginalis with metronidazole in the late second or third trimester of pregnancy may increase rates of PTB [181,182]. Vaginal candidiasis has not been shown to be a risk factor for PTB, and treatment appears to be safe in pregnancy [183]. Overall, the treatment of STIs and UTIs has not been shown to reduce the rate of PTB, but treatment of UTIs in early pregnancy confers both maternal and neonatal benefit.…”
Section: Addressing Infection: Trials Of Antibiotics To Prevent Ptbmentioning
confidence: 99%
“…Although metronidazole is safe for use in the first trimester of pregnancy, there is concern that treatment of T. vaginalis with metronidazole in the late second or third trimester of pregnancy may increase rates of PTB [181,182]. Vaginal candidiasis has not been shown to be a risk factor for PTB, and treatment appears to be safe in pregnancy [183]. Overall, the treatment of STIs and UTIs has not been shown to reduce the rate of PTB, but treatment of UTIs in early pregnancy confers both maternal and neonatal benefit.…”
Section: Addressing Infection: Trials Of Antibiotics To Prevent Ptbmentioning
confidence: 99%
“…Regarding the first point, the literature looking at candidiasis and preterm birth is inconsistent. A current meta-analysis [25] does not see any significant relation between the two and was not quoted in the current guidelines of September 2020. The literature [26][27][28] on which the recommendation is based does not support the assumption.…”
Section: Repeated Candidiasis Is a Risk Factor For Preterm Birth 2 Tmentioning
confidence: 73%
“…In cases of vaginal candidiasis, a recent systematic review found no association between asymptomatic vaginal candidiasis and PTB [ 27 ]. In other studies, however, treatment of asymptomatic candidiasis is advised in order to prevent PTB [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, however, treatment of asymptomatic candidiasis is advised in order to prevent PTB [ 28 , 29 ]. As shown in Schusters systematic review, this effect is more likely due to the anti-inflammatory effect of the treatment rather than its anti-fungal treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%